MODULAR APPROACH TO TEACHING AND LEARNING ENGLISH GRAMMAR IN TECHNICAL UNIVERSITIES - Ibyatova, Lyaysan; Oparina, Kseniya; Rakova, Elena (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The aim of this research is to find out the effectiveness of a modular approach in teaching and learning to assess students’ performance, achievement and motivation and to decide if a modular approach is more effective than traditional methods while performing an experiment with two groups of students learning English at a technical university. The researchers consider a modular specification to be a technology in which the content is divided into a number of units or modules, each of which is examined separately. A module is considered to be a set of learning opportunities organized around a well-defined topic which contains elements of instruction, specific objectives, learning activities and self-assessment and evaluation using criteria-referenced measurement. This project combines quantitative and qualitative research methods to address the impact of modular teaching, learning and assessment on engineering students. The authors use a unique modular system and their own book on English Grammar.This experiment shows that students of modular syllabuses find it useful and motivating and say that it encourages them to do better on the next modules. At the same time, modular learning and assessment does not remove the stress and workload of traditional approaches. Teachers in the modular system appreciate the better planning opportunity around the exams and the clarity of the focus of their teaching requirements. Still, the approach and the structure of modules used in the experiment requires improvement and development.